Contrasting Fe speciation in two humid forest soils: Insight into organomineral associations in redox-active environments. (1st October 2018) - Coward, Elizabeth K.; Thompson, Aaron; Plante, Alain F.
Abstract: While the contribution of iron (Fe)-bearing minerals to organic carbon (C) stabilization in terrestrial systems is well-described, the influence of Fe solid-phase speciation on organomineral associations is unclear in highly dynamic, oxidation-reduction (redox)-active soils. In humid tropic forest soils, fluctuations in redox state accelerate weathering of Fe-bearing mineral phases, producing a spectrum of mineral sizes and bonding environments available for C stabilization, and confounding our understanding of C stability. Characterizing these Fe-bearing phases can improve predictions of the response of redox-active soil systems to climatic changes that may alter Fe mineral crystallinity and solubility, such as precipitation intensity, storm event frequency and temperature. Leveraging inorganic selective dissolution techniques, 57 Fe Mössbauer spectroscopy (MBS), specific surface area (SSA) analyses and X-ray diffraction (XRD), we investigated mineral speciation in surface soils of contrasting lithologies from the Luquillo Critical Zone Observatory (LCZO), Puerto Rico. The LCZO provides a model investigatory framework in which high C inputs to surface horizons by similar vegetation, topography and climatic forcings are intercepted by highly-weathered, volcaniclastic Oxisols or quartz diorite-derived Inceptisols, producing a gradient of Fe content and speciation. Strong correlations observed between Fe concentrations and extraction-induced changes in SSA indicated target Fe phases contribute substantially to SSA of the bulk mineral matrix. MBS analysis of untreated soils reveal both Oxisol and Inceptisol soils are largely composed of Fe III -oxyhydroxides, accompanied by substantial Fe II and silicate Fe III contributions in Inceptisol soils. Fe III -oxyhydroxides in the Oxisol soils were largely short-range-ordered (SRO), and notably, a fraction of particularly low-crystallinity Fe III -oxyhydroxide mineral phases in these soils appear protected against harsh reductive dissolution, whereas the overall higher crystallinity Fe phases in the Inceptisol soils do not. These findings suggest that some high-SSA, SRO Fe III phases, which likely also have high C sorption capacities, may be immobilized against reduction in these Oxisol soils. Consequently, C associated with these Fe III phases may be preferentially stabilized in Oxisol soils, potentially driving disparate C mineralization and CO2 production rates across contrasting lithologies.